Effect of Three Different Muscle Action Training Protocols on Knee Strength Ratios and Performance. Issue 8 (August 2018) - Ruas, Cassio V.; Brown, Lee E.; Lima, Camila D.; Costa, Pablo B.; Pinto, Ronei S.
Abstract : Abstract: Ruas, CV, Brown, LE, Lima, CD, Costa, PB, and Pinto, RS. Effect of three different muscle action training protocols on knee strength ratios and performance. J Strength Cond Res 32(8): 2154–2165, 2018—Hamstring to quadriceps (H:Q) ratios are often used to assess strength imbalances. The aims of this study were to compare 3 different muscle action training protocols on H:Q strength balance and functional performance. Forty untrained men (age: 22.87 ± 2.28 years, mass: 70.66 ± 11.049 kg, ht: 174.29 ± 6.90 cm) performed 6 weeks of training on an isokinetic dynamometer. They were randomly assigned to one of 4 groups; concentric quadriceps and concentric hamstring (CON/CON), eccentric quadriceps and eccentric hamstring (ECC/ECC), concentric quadriceps and eccentric hamstring (CON/ECC), or no training. Mixed Factor analyses of variance were used to compare interactions for variables pretest and posttest between groups ( p ⩽ 0.05). The ECC/ECC group showed significant increases in H:Q functional ratio (pre = 0.73 ± 0.092, post = 0.87 ± 0.098), ECC peak torque (PT) (pre = 226.44 ± 67.80 N·m, post = 331.74 ± 54.44 N·m), isometric PT (IPT) (pre = 173.69 ± 41.41 N·m, post = 203.091 ± 30.82 N·m), countermovement jump (CMJ) (pre = 52.73 ± 6.95 cm, post = 58.16 ± 6.10 cm), and drop jump (DJ) (pre = 52.91 ± 6.080 cm, post = 58.20 ± 7.72 cm), whereas the CON/CON group increased the rate of torque development (pre = 152.19 ± 65.0074 N·m·s −1, post = 225.26 ± 88.80 N·m·s −1 ). There were no differences between groups for CON PT, squat jump, conventional ratio or 40 m sprint. Our findings suggest that ECC/ECC training may be the most effective at increasing functional H:Q strength ratios, as well as ECC PT, IPT, CMJ, and DJ performance. Eccentric training increases ECC PT, thereby increasing the functional H:Q ratio. Eccentric training also improves vertical jumping involving ECC actions. CON/CON training may be more effective at increasing explosive muscle strength.